2014
DOI: 10.3109/15412555.2014.948998
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Airflow Obstruction in U.S. Adults Aged 40–79 Years: NHANES Data 1988–1994 and 2007–2010

Abstract: Background-The study evaluated the change in the prevalence of airflow obstruction in the U.S. population 40-79 years of age from years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
5
20
0
Order By: Relevance
“…However, other larger, population-based studies have found poor correlation between self-report and measured airflow obstruction, with COPD being substantially underreported [31], and may be more so among blacks than whites [32]. With that being said, the prevalence of COPD found in the current study between 2.4% and 7.0% among nonsmokers is consistent with that reported based on measured airflow obstruction in the US among older nonsmoking adults [33] and in other general populations of nonsmokers [31]. Moreover, while underreporting (and underdiagnosis) may be higher in some groups than others due to lack of access to medical care, we found that controlling for medical care coverage had little effect on the relationships between sex and race and COPD.…”
Section: Discussionsupporting
confidence: 86%
“…However, other larger, population-based studies have found poor correlation between self-report and measured airflow obstruction, with COPD being substantially underreported [31], and may be more so among blacks than whites [32]. With that being said, the prevalence of COPD found in the current study between 2.4% and 7.0% among nonsmokers is consistent with that reported based on measured airflow obstruction in the US among older nonsmoking adults [33] and in other general populations of nonsmokers [31]. Moreover, while underreporting (and underdiagnosis) may be higher in some groups than others due to lack of access to medical care, we found that controlling for medical care coverage had little effect on the relationships between sex and race and COPD.…”
Section: Discussionsupporting
confidence: 86%
“…A limitation of this study is that no data were available to validate information on self-reported occupational exposure. Furthermore, use of reference equations developed from NHANES III data may lead to overestimation of the prevalence of airflow obstruction 1. Even by combining data from the NHANES 2007–2008 and 2009–2010 survey cycles to improve the reliability of prevalence estimates, the prevalence estimates for some occupation groups were unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…The National Center for Health Statistics (NCHS) conducted NHANES, using a multistage probability sampling design to survey a representative sample of the civilian non-institutionalised US population 6 7. We used publicly available data from the household interview survey and the standardised physical examinations conducted in mobile examination centres (MEC) 1 6 7. In the 2007–2010 NHANES, 11 891 persons aged 18–79 years who provided interview data were eligible for the spirometry component of the physical examination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Further descriptions of methods for spirometry testing, interpretation, and defining airflow obstruction have been described previously. 27 …”
Section: Methodsmentioning
confidence: 99%